2011
DOI: 10.1017/s1047951111000473
|View full text |Cite
|
Sign up to set email alerts
|

Infection and white matter injury in infants with congenital cardiac disease

Abstract: More than 60 percent of newborns with severe congenital heart disease develop perioperative brain injuries. Known risk factors include: preoperative hypoxemia, cardiopulmonary bypass characteristics, and postoperative hypotension. Infection is an established risk factor for white matter injury in premature newborns. In this study, we examined term infants with congenital heart disease requiring surgical repair to determine whether infection is associated with white matter injury. Acquired infection was specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…The association between infection and WMI has been observed before in both neonates undergoing cardiac surgery and preterm neonates. 18,23 Furthermore, the use of diuretics was much more common in the UMCU group. Although commonly administered to treat tachypnea and pulmonary edema, diuretics carry a risk of reducing preload and further compromising systemic perfusion, which may result in a higher prevalence of WMI.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The association between infection and WMI has been observed before in both neonates undergoing cardiac surgery and preterm neonates. 18,23 Furthermore, the use of diuretics was much more common in the UMCU group. Although commonly administered to treat tachypnea and pulmonary edema, diuretics carry a risk of reducing preload and further compromising systemic perfusion, which may result in a higher prevalence of WMI.…”
Section: Discussionmentioning
confidence: 98%
“…1,7,18 For our analysis, UCSF and UBC were considered a single center owing to the smaller sample size of patients with arch obstruction at UBC (n = 10) and initial comparisons showing similar perioperative management at these 2 centers (Table I; available at www.jpeds.com). Informed consent was obtained from all participating parents and from the institutional Medical Ethical Boards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Similarly, previous MRI studies performed after neonatal cardiac surgery have found that lower postoperative blood pressure, regional cerebral saturation, and a preceding infection are associated with the occurrence of new lesions. 5,8,24 Animal models of CPB underscore this and have found that lower oxygenation and higher inflammation lead to more WMI. Hence, as proposed by Andropoulos et al, 5 a targeted protocol aiming for acceptable postoperative regional cerebral saturation values may be necessary to ensure adequate cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were conducted in tertiary urban or teaching hospitals. Among studies conducted in highincome settings, 15 were in European countries, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] 19 in the United States of America, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] one in Australia, 36 three elsewhere in North America, [37][38][39] and three in Asia. [40][41][42] There were three nonrandomised interventional studies, 6,22,23 32 cohort studies, [2][3][4][5][7][8]...…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%